ANALISIS PEMBENTUKAN PORTOFOLIO OPTIMAL PADA SUB SEKTOR PERKEBUNAN DAN SUB SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - MUSLIMAH, LATIFAH (Fakultas Ekonomi Universitas Tadulako, 2016)
This study aims to determine the combination of optimal portfolios on plantation sub-sector and banking sub-sector listed on the Indonesia Stock Exchange, which is undertaken by looking at the level of the expected return and risk (standard deviation) generated by a combination of the portfolio each year. The main issue raised in this research is how the combination of the optimal portfolio can be formed from plantation sub-sector and banking sub-sector listed on the Indonesia Stock Exchange in 2010-2014. The research applied Coefficient of Variation (CV) as a research method to determine the probability of shares in each sub-sector for each company combined, as well as efficient portfolio, so that the optimal portfolio can be formed easily. The results show that the determination of the portfolio using the optimal portfolio yield probability SMAR shares of 0.05 or 5% and the probability of SDRA shares of 0.95 or 95% to portfolio risk by 0.460 and the expected return of the portfolio amounted to 0.393. The portfolio combination that is not optimal produces probability GZCO shares amounting to -0.19% and the probability of SDRA shares of 1.19% to portfolio risk and return expectations of 0.472 at 0.569.